Improvement of signal-to-noise ratio of a beat note by cascading an Yb-doped fiber amplifier in an Er-fiber comb. (14th September 2017) - Liu, H; Cao, S Y; Yu, Y; Lin, B K; Lu, W P; Fang, Z J
Abstract: Femtosecond optical frequency combs (FOFCs) make it possible to measure the absolute frequency of a laser, which greatly simplifies quantity traceability and comparison of the absolute frequency. In order to ensure the accuracy and reliability of the measurement, the signal-to-noise ratio (SNR) of the beat note ( f b ) between an FOFC and a laser should be above 30 dB. In this paper, an Er-doped FOFC (Er-FOFC) is employed, at a repetition rate of 305 MHz. The spectral intensity near the 1 µ m wavelength in an octave-spanning supercontinuum generated from the Er-FOFC is enhanced effectively by cascading an Yb-doped fiber amplifier after spectral broadening, which helps improve the SNR of the beat note between the comb light and an iodine-stabilized 532 nm laser. This method can effectively reduce the intensity requirements on the 1 µ m wavelength when the spectrum is directly broadened in an Er-FOFC.